2022
DOI: 10.6004/jnccn.2022.7039
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Response to Erdafitinib in FGFR2-Mutated Metastatic Pancreatic Ductal Adenocarcinoma

Abstract: Despite advances in cancer therapeutics, pancreatic ductal adenocarcinoma (PDAC) remains among the deadliest malignancies, with a poor prognosis at time of diagnosis. Research in PDAC has suggested that adaptive signaling in the tumor microenvironment may promote tumor proliferation and survival. Several FGFR fusion genes—specifically FGFR2—are involved with the creation and progression of cancer. These mutations are found in a variety of cancer types. This report presents a unique case of a young patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A recent case report showed durable response of >12 months with erdafitinib in a young male with relapsed FGFR rearranged PDA. Incidentally, the patient in that particular case was also KRAS wild-type ( 52 ). The authors mention that the pathology revealed poorly differentiated adenocarcinoma, raising the possibility of it being a cholangiocarcinoma, as FGFR GA is more common in biliary tract cancers ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent case report showed durable response of >12 months with erdafitinib in a young male with relapsed FGFR rearranged PDA. Incidentally, the patient in that particular case was also KRAS wild-type ( 52 ). The authors mention that the pathology revealed poorly differentiated adenocarcinoma, raising the possibility of it being a cholangiocarcinoma, as FGFR GA is more common in biliary tract cancers ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 91%
“…Incidentally, the patient in that particular case was also KRAS wild-type ( 52 ). The authors mention that the pathology revealed poorly differentiated adenocarcinoma, raising the possibility of it being a cholangiocarcinoma, as FGFR GA is more common in biliary tract cancers ( 52 , 53 ). FGFR2 GAs, which are mostly fusions, are found in 10-15% of intrahepatic cholangiocarcinoma’s ( 53 ), compared to 4.4% in our KRAS wild-type PDA cohort.…”
Section: Discussionmentioning
confidence: 91%
“…Promising pilot clinical studies have shown complete responses in small numbers of PDAC patients treated with pan‐FGFRi (Ng et al, 2022; Poon et al, 2021; Subbiah et al, 2022). Here we show that FGFR1 expression is a key factor in determining single‐agent pan‐FGFRi efficacy in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical case reports have shown complete responses of metastatic PDAC patients to single-agent FGFRi (Ng et al, 2022;Poon et al, 2021;Subbiah et al, 2022). However, the therapeutic utility of selective FGFRi in PDAC is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation